CYTOGENETIC STUDIES ON THE SUBFAMILY HYPOPTOPOMATINAE (PISCES, SILURIFORMES, LORICARIIDAE) .3. ANALYSIS OF 7 SPECIES - Andreata, A. A.; Dealmeidatoledo, L. F.; Oliveira, C.; Dealmeidatoledo, S. (Univ Florence Botany Inst, 1994)
Cytogenetic studies carried out on nine species belonging to five genera of the subfamily Hypoptopomatinae showed that this group has a relatively constant diploid number, 2n = 54, with only one species having 2n = 72 chromosomes. Nevertheless, the karyotypic formulae, NOR position and C-band pattern are very different among species and sometimes among local populations, with species having undifferentiated sex chromosomes and species having the XX/XY or the ZZ/ZW mechanisms. The population structure of species belonging to the subfamily Hypoptopomatinae suggests that many chromosome rearrangements have been fixed in the different species and populations due to their geographic isolation and these karyotypic differences may be very important today for species definition.
Keywords: KARYOTYPE; NOR; C-BAND; SEX CHROMOSOMES; LORICARIIDAE